DETERMINATION OF OXYGEN CONTENT IN COPPER BY MEANS OF COMPUTER ANALYSIS OF IMAGES - A. G. Anisovich; I. N. Rumjantseva; P. N. Misuno (Литьë и металлургия)
The possibility of determination of oxygen concentration in cast copper in program «IMAGE SP» is considered. It is shown the satisfactory compliance with results, received under state standard specification 13938.13-93. The advantages of computer methods of analysis are demonstrated.